FOOD AND FEEDING HABIT OF OREOCHROMIS NILOTICUS (LINNAEUS, 1758) FROM RIVER OKURA AT OFEJIJI, KOGI STATE, NIGERIA - Onimisi, Meriyamoh Mero (FUDMA JOURNAL OF SCIENCES, 2025)
The food and feeding habit of Oreochromis niloticus (Linnaeus, 1758) from River Okura was studied from October, 2010 to September 2011. Three hundred and sixty eight (368) samples of Oreochromis niloticus were collected forth - nightly from the local fishermen. The fish were caught with gillnets of mesh size 4.5cm x 4.5cm and gura traps. The fish were weighed, measured and dissected out for their guts. The guts were weighed and length of the gut was taken to the nearest 0.1g and 0.1cm respectively. Gut fullness was estimated visually and categorized. Analysis of the gut content was by frequency of occurrence and numerical methods. Out of 368 O. niloticus examined, 8.7% were completely empty guts while 58.5% of the guts had fullness of above 50% throughout the year. The mean gut fullness showed a significant variation throughout the season. Feeding intensity in the species is observed to be high in the months of July, August and September corresponding to the late rainy season when there was abundance of food. The species fed mainly on phytoplankton and detritus. It consumed a few zooplankton. The phytoplankton consumed include Microcystis spp, Anabaena spp, Chlamydomonas, Merismopedia spp (Cyanophyceae), Diatoma spp, Navicula spp, Melosira spp, (Baccillariophyceae),Closterium spp and Staurastrum spp. (Chlorophyceae). The gut length of O.niloticus is averagely 8.2 times the standard body length characterizing it to be herbivorous. Detritus which is a dominant food item in the gut of the species is considered to be majorly plant materials at various levels of digestion.
Keywords: Species; Fullness; Food; Detritus; Gut; Feeding